Examining the Effect of Residential Mobility on Crime Through the Mechanism of Perceived Informal Social Costs - Kijowski, Matthew C. (Crime & delinquency, 2022)
Although research suggests a positive association between adolescent residential mobility and offending, the mechanism by which this process unfolds is less understood. One commonly cited explanation is that moving severs ties to pro-social others, reducing perceptions of informal social costs that then leads to offending. We test this mechanism with data from the Pathways to Desistance Study, which is a longitudinal study of serious offending youth. We integrate monthly-level residential mobility information from the access-restricted Life Event Calendar data with the publicly available data comprised of informal social costs and offending. We estimate fixed effects models with bootstrapping techniques to produce point estimates of the indirect effect. Our results provide insight into a prominent mechanism by which mobility affects offending.